Why should we care about edaphic springtails? Por que devemos nos importar com os colêmbolos edáficos? - Filho L.C.I.O. (2016)
The current research aims to introduce the importance of springtails edaphic, with particular reference to agronomic and ecological aspects. General characteristics, density and distribution of springtails, and the relationship of Collembola with agricultural practices, fungi, nutrient cycling and soil fertility were covered in this study. Moreover, some literature data have been reported to demonstrate the importance of these organisms to ecosystem services such as nutrient cycling, improved fertility, soil aggregation, fungus control and indicators of soil quality. This research aims demonstrate the important role of springtails and expand the investigation field with these organisms, increasing knowledge of the important processes mediated by them and the interface between the Soil Ecology and Soil Science.